Studi pengawasan akademik proses belajar mengajar matematika oleh Kepala SDN Kecamatan Ciawi Kabupaten Tasikmalaya - Ebih Abdul Rachim Arhasy; Eva Mulyani (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2018)
ABSTRAK This research was conducted to describe the implementation of supervision  of mathematics academic conducted by principal of elementary school in mathematics subject. This is done to review realistically about the implementation of supervision  academic. This supervision is essentially to foster teachers in improving the quality of the learning process. This descriptive research was conducted on the Head of Primary School at UPT Education and Culture of Ciawi Sub-district of Tasikmalaya Regency. Based on the results of the research indicates that the implementation of academic supervision on mathematics subjects in Ciawi District Elementary School runs quite well but has not shown optimal results in terms of learning planning, learning implementation plan, classroom learning implementation, findings of observations and problems found has not been fully inventoried. Keywords: Implementation; Academic supervision; Mathematical lessons; Primary school